Design Modification of the Combi-type Body Considering the Impact on Vehicle Aerodynamics - Case Study - Fabian, Michal; Huňady, Róbert; Lagos, Orlando (Manufacturing Technology Journal, 2023)
Car manufacturers are constantly looking for new options to make the vehicle more attractive to the cus-tomer. In terms of design, this is usually done in the middle of a model's life cycle, when a so-called facelift of a production model is carried out. This involves small changes to the shape of the bodywork to improve the design of the vehicle until it is time for a new model range. This paper discusses a case study that focuses on the modification of the rear body components of a ŠKODA Superb III in Combi version. The aim of the study is to assess how the proposed modifications will affect the aerodynamics of the vehicle. The most sig-nificant changes concern the rear spoiler and finlets. The aerodynamic properties are assessed based on CFD simulations that are performed for a series production and a modified variant of the vehicle, and the results of which are compared and discussed.
Keywords: Vehicle aerodynamics; CFD simulation; Air drag coefficient; Combi-type body; Design modification; Spoiler; Finlet